The H i content of dark matter haloes at z ≈ 0 from ALFALFA. Issue 4 (24th April 2019) - Obuljen, Andrej; Alonso, David; Villaescusa-Navarro, Francisco; Yoon, Ilsang; Jones, Michael
ABSTRACT: We combine information from the clustering of H i galaxies in the 100 per cent data release of the Arecibo Legacy Fast ALFA survey, and from the H i content of optically selected galaxy groups found in the Sloan Digital Sky Survey to constrain the relation between halo mass Mh and its average total H i mass content M H i . We model the abundance and clustering of neutral hydrogen through a halo-model-based approach, parametrizing the M H i ( Mh ) relation as a power law with an exponential mass cut-off. To break the degeneracy between the amplitude and low-mass cut-off of the M H i ( Mh ) relation, we also include a recent measurement of the cosmic H i abundance from the α.100 sample. We find that all data sets are consistent with a power-law index α = 0.48 ± 0.08 and a cut-off halo mass $\log _{10}M_{\rm min}/(h^{-1}\mathrm{ M}_\odot)=11.18^{+0.28}_{-0.35}$ . We compare these results with predictions from state-of-the-art magnetohydrodynamical simulations, and find both to be in good qualitative agreement, although the data favours a significantly larger cut-off mass that is consistent with the higher cosmic H i abundance found in simulations. Both data and simulations seem to predict a similar value for the H i bias ($b_{\rm H\, {\small I}}=0.878^{+0.022}_{-0.023}$ ) and shot-noise power ($P_{\rm SN}=94^{+20}_{-18}\, [h^{-1}\, {\rm Mpc}]^3$ ) at redshift z = 0.